Increased Cortical Porosity and Reduced Trabecular Density Are Not Necessarily Synonymous With Bone Loss and Microstructural Deterioration. (4th October 2018) - Zebaze, Roger; Atkinson, Elizabeth J; Peng, Yu; Bui, Minh; Ghasem‐Zadeh, Ali; Khosla, Sundeep; Seeman, Ego
Abstract: Absolute values of cortical porosity and trabecular density are used to estimate fracture risk, but these values are the net result of their growth‐related assembly and age‐related deterioration. Because bone loss affects both cortical and trabecular bone, we hypothesized that a surrogate measure of bone fragility should capture the age‐related deterioration of both traits, and should do so independently of their peak values. Accordingly, we developed a structural fragility score (SFS), which quantifies the increment in distal radial cortical porosity and decrement in trabecular density relative to their premenopausal mean values in 99 postmenopausal women with forearm fractures and 105 controls using HR‐pQCT. We expressed the results as odds ratios (ORs; 95% CI). Cortical porosity was associated with fractures in the presence of deteriorated trabecular density (OR 2.30; 95% CI, 1.30 to 4.05; p = 0.004), but not if trabecular deterioration was absent (OR 0.96; 95% CI, 0.50 to 1.86; p = 0.91). Likewise, trabecular density was associated with fractures in the presence of high cortical porosity (OR 3.35; 95% CI, 1.85 to 6.07; p < 0.0001), but not in its absence (OR 1.60; 95% CI, 0.78 to 3.28; p = 0.20). The SFS, which captures coexisting cortical and trabecular deterioration, was associated with fractures (OR 4.52; 95% CI, 2.17 to 9.45; p < 0.0001). BMD was associated with fracture before accounting for the SFS (OR 5.79; 95% CI, 1.24 to 27.1; p = 0.026), not after (OR 4.38; 95% CI, 0.48 to 39.9; p = 0.19). The SFS was associated with fracture before (OR 4.67; 95% CI, 2.21 to 9.88) and after (OR 3.94; 95% CI, 1.80 to 8.6) accounting for BMD (both p s < 0.0001). The disease of bone fragility is captured by cortical and trabecular deterioration: A measurement of coexisting cortical and trabecular deterioration is likely to identify women at risk for fracture more robustly than absolute values of cortical porosity, trabecular density, or BMD. © 2018 The Authors. JBMR Plus Published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research